Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                
0% found this document useful (0 votes)
83 views

ECE-223, Solutions For Assignment #2

This document contains solutions to various problems involving simplifying Boolean expressions and converting between sum of products and product of sums forms. Some key steps include simplifying expressions using Boolean algebra rules like idempotency, complement, absorption and distribution. Truth tables are used to represent functions and their canonical forms. Logic diagrams are drawn from the original and simplified expressions. Commutativity and associativity properties of binary operations like inhibition and XOR are proven using their Boolean expressions.

Uploaded by

Leo
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
83 views

ECE-223, Solutions For Assignment #2

This document contains solutions to various problems involving simplifying Boolean expressions and converting between sum of products and product of sums forms. Some key steps include simplifying expressions using Boolean algebra rules like idempotency, complement, absorption and distribution. Truth tables are used to represent functions and their canonical forms. Logic diagrams are drawn from the original and simplified expressions. Commutativity and associativity properties of binary operations like inhibition and XOR are proven using their Boolean expressions.

Uploaded by

Leo
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 4

ECE-223, Solutions for Assignment #2

Chapter 2, Digital Design, M. Mano, 3rd Edition

2.2)
Simplify the following Boolean expression to a minimum number literals:
a) xy + xy′
b) (x + y)(x + y′)
c) xyz + x′y + xyz′
d) (A+B)′(A′+B′)′

a) xy + xy′ = x ( y+y′)= x.1 = x


b) (x+y)(x+y′) = xx + xy′ + yx+yy′ = x + xy′ + xy + 0 = x (1+ y′ + y) = x.1= x
Also (x+y)(x+y′) =x+ yy′ = x + 0 = x
c) xyz + x′y + xyz′ = xy(z+z′) + x′y = xy +x′y = y(x+x′)=y
d) (A+B)′(A′+B′)′= (A′B′).(AB) = 0

2.3)
Simplify the following Boolean expression to a minimum number literals:
a) ABC + A′B + ABC′
b) x′yz + xz
c) (x+y)′(x′+y′)
d) xy + x(wz + wz′)
e) (BC′+A′D)(AB′+CD′)

a) ABC + A′B + ABC′ = AB(C+C′) + A′B = AB + A′B = B(A+A′) = B


b) x′yz + xz = z(x′y+x)= z(x′+x)(x+y) = z(x+y)
c) (x+y)′(x′+y′) = x′y′.(x′+y′) = x′y′+x′y′ = x′y′
d) xy + x(wz + wz′) = xy + xw(z+z′) = xy + xw = x(y+w)
e) (BC′+A′D)(AB′+CD′)= AB′BC′ + AB′A′D + CD′BC′ + CD′A′D = 0

2.6)
Find the complement of the following expressions:

a) xy′+x′y
b) ( AB′+C)D′+E
c) (x+y′+z)(x′+z′)(x+y)

Page: 1
a) [xy′+x′y]′ = (xy′)′ + (x′y)′ = (x′+y).(x+y′) = xx′ + yy′
b) [(AB′+C)D′+E]′ = [(AB′+C)D′]′.E′ = [(AB′+C)′+D] . E′= [(A′+B).C′ +D].E′ =
= (A′+B+D).(C′+D).E′
c) [(x+y′+z)(x′+z′)(x+y)]′ = (x+y′+z)′+(x′+z′)′+(x+y)′= x′yz′ + xz + x′y′

2.7)
Given Boolean function F1 and F2.
a) Show that the Boolean function E = F1+F2 contains the sum of the minterms of F1 and
F2
b) Show that the Boolean function G = F1.F2 contains the sum of the minterms of F1 and
F2

F1= ∑ mi and F2= ∑ mj


a)
E = F1+ F2= ∑ mi + ∑ mj = ∑ (mi + mj)

b)
G = F1F2 = ∑ mi . ∑ mj
mi.mj = 0 if i ≠ j
mi.mj = 1 if i = j
Therefore G has only common minterms.

2.14)
Obtain the truth table of the following functions and express each function in sum of
minterms and product of maxterms:

a) (xy + z) ( y + xz)
b) (A′ + B) (B′+C)
c) y′z + wxy′ + wxz′ + w′x′z

a) (xy + z) ( y + xz) = xy + yz + xyz + xz =∑(3,5,6,7) = ∏ ( 0 ,1,2,4)


b) (A′ + B) (B′+C) = A′B′ + A′C + BC = ∑ (0,1,3,7) = ∏ ( 2,4,5,6)
c) y′z + wxy′ + wxz′ + w′x′z = ∑(1,3,5,9,12,13,14)= ∏ (0,2,4,6,7,8,10,11,15)

2-15)
Given the Boolean function
F= xy′z + x′y′z + w′xy + wx′y + wxy
a) Obtain the truth table of the function.
b) Draw the logic diagram using the original Boolean expression.

Page: 2
c) Simplify the function to a minimim number of literals using Boolean algebra.
d) Obtain the truth table of the function from the simplified expression and show that it
is the same as the one in part (a)
e) Draw the logic diagram from the simplified expression and compare the total number
of gates with the diagram of part (b)

a) F(w,x,y,z) = ∑ ( 1,5,6,7,9,10,11,13,14,15)

b) F= xy′z + x′y′z + w′xy + wx′y + wxy


5 3-input AND gate; 5 3-input OR gate
c) F = y′z(x+x′) + xy(w′+w) + wy(x′+x) = y′z + xy + wy = y′z + y ( x + w)

d) F(w,x,y,z) = ∑ ( 1,5,6,7,9,10, 11,13,14,15)

e) y'
z
F
y
x
w

2.17)
Express the complement of the following function in sum of minterms:
a) F(A,B,C,D) = ∑(0,2,6,11,13,14)
b) F(x,y,z) = ∏(0,3,6,7)

a) F′(A,B,C,D) = ∑(1,3,4,5,7,8,9,10,12,15)

b) F′(x,y,z) = ∑(0,3,6,7)

2.18)
Convert the following to the other canonical form:
a) F(x,y,z) = ∑(1,3,7)
b) F(A,B,C,D) = ∏ (0,1,2,3,4,6,12)

a) F(x,y,z) = ∑(1,3,7) = ∏(0,2,4,5,6)


b) F(A,B,C,D) = ∏ (0,1,2,3,4,6,12) = ∑(5,7,8,9,10,11,13,14,15)

Page: 3
2.22)
By substituting the Boolean expression equivalent of the binary operation as defined in
Table 2-8 ( Digilal Design, M. Mano, 3rd Edition,pp. 57) show the following:
a) The inhibition operation is neither commutative nor associative.
b) The exclusive-OR operation is commutative and associative.

a) x/y = xy′ ≠ y /x = x′y Not Commutative


(x/y)/z = xy′z′ ≠ x/(y/z) = x(yz′)′ = xy′ + xz Not Associative

b) x ⊕ y = xy′ + x′y = y ⊕ x = yx′ + y′x Commutative


(x ⊕ y) ⊕ z = ∑(1,24,7) = x ⊕ (y ⊕ z) Associative

Page: 4

You might also like